2012
DOI: 10.1093/cercor/bhs199
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl Endopeptidase-Deficient Mice Have Reduced Synaptic Spine Density in the CA1 Region of the Hippocampus, Impaired LTP, and Spatial Learning and Memory

Abstract: Prolyl endopeptidase (PREP) is a phylogenetically conserved serine protease and, in humans and rodents, is highly expressed in the brain. Several neuropeptides associated with learning and memory and neurodegenerative disorders have been proposed to be the substrates for PREP, suggesting a possible role for PREP in these processes. However, its physiological function remains elusive. Combining genetic, anatomical, electrophysiological, and behavioral approaches, we show that PREP genetrap mice have decreased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…In the central nervous system, Prep mRNA was found in the hypothalamus (Fig. 1A), hippocampus, and cortex (5,6). Within the hypothalamus, higher expression of Prep mRNA was detected in the ventromedial nucleus (VMH) (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In the central nervous system, Prep mRNA was found in the hypothalamus (Fig. 1A), hippocampus, and cortex (5,6). Within the hypothalamus, higher expression of Prep mRNA was detected in the ventromedial nucleus (VMH) (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Prep gt/gt male mice were perfused with 4% paraformaldehyde. Brains were sectioned (50 μm), washed in PBS, and incubated overnight at 37°C in the staining solution containing 25 mM K 3 Fe(CN) 6 , 25 mM K 4 Fe (CN) 6 3H2O, 2 mM MgCl 2 in PBS, and 1 mg/mL of X-Gal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it was suggested that PREP may be released from the cells (Ahmed et al, ), even though it lacks a secretion signal and it does not contain a transmembrane region, or a lipid anchor sequence (Venäläinen et al, ). PREP has been implicated in several biological processes, including cognitive disorders (Rossner et al, ; Hannula et al, ), celiac disease (Siegel et al, ; Comino et al, ), cell death (Bär et al, ; Matsuda et al, ), learning and memory (Irazusta et al, ; D'Agostino et al, ), cell proliferation and differentiation (Matsubara et al, ; Suzuki et al, ), and glucose metabolism (Kim et al, ). However, its physiological role remains to be elucidated.…”
mentioning
confidence: 99%
“…In the healthy brain, PREP is present mostly in neurons: in the cytoplasm, around the nucleus along the microtubules, and at the tips of the neurites. 23,24 PREP overexpression has been shown to reduce the levels of polysialylated neural cell adhesion molecule (PSA-NCAM), whereas in PREP-negative mice, PSA-NCAM level was increased. 17 PREP expression is also upregulated in glial cells after activation with lipopolysaccharide (LPS) 13 and is found to be neurotoxic to co-cultured neuronal cells, an effect that was reversed by PREP inhibitors.…”
Section: Introductionmentioning
confidence: 99%